Dynamics of IUD use in Vietnam: implications for family planning services at primary health care level - Park MH; Nguyen TH; Ngo TD (Dove Medical Press, 2011)
Min Hae Park1,2, Thang Huu Nguyen3, Thoai Dinh Ngo1,21Research and Metrics Team, Health System Department, Marie Stopes International; 2Faculty of Epidemiology and Population Health, London School of Hygiene and Tropical Medicine, London, UK; 3Research and Metrics Team, Marie Stopes International Vietnam, Ha Noi, VietnamAbstract: This study describes the dynamics of intrauterine device (IUD) use in Vietnam and implications for family planning services. A retrospective study was conducted among women who received IUD services in 2006–2009 at six commune health stations in three provinces. Women were interviewed about IUD use and switching behaviors. Of 1316 participants, 12.1% had discontinued IUD use at 12 months after insertion, 19.4% at 24 months, and 26.9% at 36 months. The highest rates of discontinuation were among older women and farmers/manual workers. Among 434 women who had an IUD removed, 49% cited health concerns as the main reason. Following removal, 70% switched to another contraceptive method (n = 306); of these, 15% switched to withdrawal, and 12% waited >2 months before adopting a new method. Dissatisfaction with IUD services was associated with high rates of discontinuation. Early discontinuation, delays in adopting new methods, and switching to withdrawal may contribute to unintended pregnancy among commune health station users in Vietnam.Keywords: intrauterine device, contraceptive discontinuation, dissatisfaction